Corporate Reputation: Building and Mantaining - Abraham Chuang-Chyi Tiong (Journal of Digital Marketing and Communication, 2022)
Within the context of a corporation, this research investigated how to construct and preserve a positive corporate reputation. Interview-based qualitative research methods were utilized to compile the information that was acquired from public relations experts working in the PR area. The purpose of this study is to investigate whether or not there are any connections between company reputation and stakeholder management. In addition, research has been carried out to discover the best way to develop communication strategies with the various sorts of stakeholders. In-depth primary research was conducted with a carefully selected respondent with the purpose of gaining an understanding of how businesses and other organizations construct and preserve their corporate reputations. The respondent was selected to ensure that the feedback obtained would be of a high quality and would reflect insight from a position that is rarely presented in public. In order to guarantee the reliability of the findings, conclusions were drawn based on the information obtained from the interviewee in addition to the findings of a number of other research and journal articles.